Pengelolaan Kelas Pembelajaran PAI Dalam Kurikulum Merdeka di SDIT Insan Kamil Bukittinggi - Gusianti, Messa; C, Charles (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Classroom management is something that is always intertwined with the teaching and learning process. With good classroom management, it is hoped that the implementation of learning can run effectively. Which in the current independent curriculum focuses on the development of student competencies and this curriculum is also more flexible. Classroom management also considers the diversity of students' learning styles in the classroom, so that students can feel comfortable, happy, and more active in their learning. The data collection process involved conducting in-depth observations and interviews with the data sources, namely the Islamic Religious Education subject teacher and the fourth-grade students of SDIT Insan Kamil Bukittinggi. The results of this study show that classroom management is carried out well, with the teacher preparing things that support the learning process and paying attention to the condition of the classroom, classroom cleanliness, as well as the selection of effective methods and media so that students can learn well. Classroom management also needs to pay attention to the diversity of students in the class; teaching must be tailored to the needs of each student because each student certainly has different learning styles. Thus, it is hoped that students can learn according to their interests and develop their talents.